Lateral intercrural suture in the caucasian nose: Decreased domal divergence angle in endonasal rhinoplasty without delivery - Berger, Cezar Augusto Sarraf; Mocelin, Marcos; Soares, Caio Márcio Correia; Pasinato, Rogério; Frota, Andreia Ellery (International Archives of Otorhinolaryngology, 2012)
Introduction: Several techniques can be performed to improve nasal tip definition such as cartilage resection, tip grafts, or sutures.Objctive: To evaluate the outcome of lateral intercrural suture at the lower lateral cartilage by endonasal rhinoplasty with a basic technique without delivery in decreasing the angle of domal divergence and improving the nasal tip definition.Method: This prospective study was performed in 64 patients in which a suture was made on the board head of the lower lateral cartilage in the joint between the dome and lateral crus, using polydioxanone (PDS) with sharp, curved needle.Results: In all of the cases, better definition of the nasal tip was achieved by intercrural suturing for at least 6 months postoperatively.Conclusion: Lateral intercrural suture of the lower lateral cartilage provides improved nasal tip definition and can be performed by endonasal rhinoplasty without delivery in the Caucasian nose.
Keywords: sutures; rhinoplasty; nasal cartilage